Characteristics and publication status of minimally invasive glaucoma surgery trials registered in ClinicalTrials.gov, 2007–2024: a cross-sectional study - Chuzhi Peng; Hongyan Jia; Jianping Hu; Yonghong Jiao (BMJ Open)
Purpose To investigate the characteristics and publication status of minimally invasive glaucoma surgery (MIGS) clinical trials registered on ClinicalTrials.gov.Design A cross-sectional study.Methods All 1212 interventional glaucoma trials registered on ClinicalTrials.gov with start dates between 1 October 2007 and 30 April 2024 were included. All trials were categorised into ‘MIGS trials’ and ‘other interventional glaucoma trials’. Based on the anatomical site of action and the research content, MIGS trials were classified into different groups, and intergroup comparisons were conducted. The characteristics and publication status of MIGS trials were comprehensively analysed.Results Compared with all other interventional glaucoma trials, MIGS trials had a higher proportion of single-arm trials (p<0.001) and industry funding (p<0.001), but a lower proportion of randomisation and blinding (p<0.001). The majority of MIGS trials were not overseen by a Data Monitoring Committee (DMC) (71.4%) and enrolled fewer than 200 participants (85.2%). MIGS trials targeting Schlemm’s canal (SC) (60.2%) were significantly more prevalent than those targeting subconjunctival space (24.6%) and suprachoroidal/supraciliary space (15.3%). Trials focused on stand-alone MIGS (48.4%) or its combination with cataract surgery (32.0%) significantly outnumbered those investigating MIGS with other antiglaucoma surgeries (12.3%), MIGS with laser treatments (4.1%) and MIGS with medications (3.3%). A total of 34 MIGS trials (27.0%) published their results, of which 20 trials focused on stand-alone MIGS.Conclusions Most MIGS trials were industry-funded, non-randomised, non-blinded and not overseen by a DMC. Researchers tend to focus on stand-alone MIGS or its combination with cataract surgery. The efficacy and safety of MIGS targeting SC remain a prominent focus of the field. Currently, the publication rate of MIGS clinical trials is relatively low. It remains difficult for ophthalmologists to choose among different MIGS procedures. Overcoming the design limitations of trials will be essential for generating more robust evidence to guide clinical practice and policy decisions.